Faktor-faktor yang berhubungan dengan penerapan Continuity of Care pada kelengkapan Pemeriksaan Kehamilan di Wilayah Kerja Puskesmas Majakarti Jaya Kabupaten Banyuasin - Harnita, Harnita; Mastina, Mastina; Effendi, Hazairin; Afrika, Eka (NHM PRESS, 2023)
The Maternal Mortality Rate (MMR) was one of the global Sustainable Development Goals (SDGs) targets to reduce the maternal mortality rate (MMR) to 70 per 100,000 live births in 2030. Factors influencing the implementation of Continuity of Care (CoC) during pregnancy included age, education, parity, employment, health insurance, family support, income, and distance. This study aimed to determine the factors related to the implementation of Continuity of Care with Completeness of Examinations during Pregnancy in the Work Area of the Makarti Jaya Health Center, Banyuasin Regency in 2023. The research design used an analytical survey with a cross-sectional approach. The population in this study was third-trimester pregnant women who came to check their pregnancies at the Makarti Jaya Health Center, Banyuasin Regency, totaling 86 people. The sampling technique in this study was carried out by purposive sampling with a total sample of 86 respondents. Data collection was done using a questionnaire sheet. Data analysis used univariate analysis and bivariate analysis used the chi-square test. The results of the study showed that there is a relationship between education (p-value = 0.011), parity (p-value = 0.026), and husband support (p-value = 0.042) with the completeness of examinations during pregnancy for pregnant women in the Working Area of the Makarti Jaya Health Center, Banyuasin Regency, in 2023. It is hoped that the results of This research can be an illustration for the health center to be able to further increase the visits of pregnant women in their working areas by providing information to pregnant women about the schedule and benefits of pregnancy checks.